Estudio preliminar de "Macrodontina", una nueva cisteinilproteinasa aislada de frutos de Pseudananas macrodontes (Morr.) Harms (Bromeliaceae) - Brullo, Adriana (1994)
From inmature fruits of Pseudananas macrodontes (Morr.) Harms, known as ihvirá in the northeast of Argentina, has been isolated and partially characterized a sulfhydril-protease highly active between pH 7 and 10. The acetonic precipitates are quite stable at temperatures below 45ºC and not affected by freezing or liophylization. Anionic exchange chromatography (DEAE-Sepharose Fast Flow) affords two active fractions, both well resolved by gel filtration (Sephadex G-75). The electrophoretic pattern (SDS-PAGE) of the acetonic precipitate shows six protein fractions, between 14 and 67 kDa, but the zymogram reveals the presente of three active fractions, of about 27,30, arid 54 kDa.